DOP73 A comparative efficacy and safety analysis of subcutaneous infliximab and vedolizumab in patients with Crohn's Disease and Ulcerative Colitis. (21st January 2022) - Peyrin-Biroulet, L; Arkkila, P; Armuzzi, A; Atreya, R; Danese, S; Ferrante, M; Guardiola, J; Jahnsen, J; Louis, E; Lukáš, M; Reinisch, W; Roblin, X; et al.
Abstract: Background: CT-P13 is the first and only subcutaneous (SC) formulation of infliximab (IFX) which received EMA approval in July 2020 for the treatment of Crohn's disease (CD) and ulcerative colitis (UC). This study compares efficacy and safety between IFX SC and vedolizumab (VDZ) in moderate-to-severe CD or UC patients using data from the pivotal study of IFX SC, VISIBLE 2 and recently presented systematic literature review and meta-analysis [1]. Methods: This comparative study analyses 7 randomised controlled trials. The IFX SC trial (NCT02883452) was compared with the VDZ trials including GEMINI II, GEMINI III, VISIBLE 2 for CD and GEMINI I, VISIBLE 1, and VARSITY for UC. VISIBLE 2 was added in this analysis as it was published after the presented meta-analysis. In all studied VDZ trials, only responders at week 6 continued to receive maintenance treatment except VARSITY trial, which followed a treat-through design. Crohn's Disease Activity Index (CDAI)-70, CDAI-100 response and clinical remission for CD, and clinical response, clinical remission, and mucosal healing for UC at week 6 (induction) and 1 year (week 50–54, maintenance) were compared between IFX SC and VDZ for evaluating efficacy. Discontinuation due to lack of efficacy and safety profiles over 1 year were also assessed. Results: In the patients with CD, IFX yielded significantly better efficacy results in the induction phase compared to VDZ with non-overlapping 95% confidential interval while IFX SC displayed better results, although statistically non-significant during the maintenance phase (Table 1). In UC, similar efficacy was shown between the treatments during both induction and maintenance phase (Table 2). The proportion of patients discontinued due to lack of efficacy was significantly higher in VDZ compared to IFX SC in both CD (IFX SC 5% and VDZ 32%) and UC (IFX SC 3% and VDZ 15%) over 1 year (Tables 1, 2). The safety profiles were generally comparable between IFX SC and VDZ. Similar proportion of patients experienced serious adverse event (9% and 14% in CD; 12% and 11% in UC in IFX SC and VDZ). The proportion of patients experiencing serious infection between the treatments was also similar in both CD and UC (Tables 3, 4). Conclusion: Better efficacy was shown in IFX SC compared to VDZ in CD, while a similar efficacy was shown in UC. A significantly higher proportion of patients were discontinued due to lack of efficacy in VDZ compared to that of IFX SC over 1 year. Safety profiles over 1 year were generally comparable between IFX SC and VDZ in both indications. Reference: 1. Peyrin-Biroulet, L. (2021). P0414 Efficacy and safety of infliximab and vedolizumab in patients with inflammatory bowel diseases: a systematic review and meta-analysis. Poster presented at: 2021 UEG Week.